A novel loss-of-function mutation in NRAP is associated with left ventricular non-compaction cardiomyopathy - Zhang, Zhongman; Xu, Kangkang; Ji, Lianfu; Zhang, Han; Yin, Jie; Zhou, Ming; Wang, Chunli; Yang, Shiwei (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Nebulin-related-anchoring protein （NRAP）gene encodes actin-associated ankyrin. Few studies reported the association of NRAP gene with cardiomyopathy. Thus, the genetic role of this gene in cardiomyopathy remains to be investigated. Methods: The clinical data of the rare case of Left ventricular non-compaction (LVNC) was collected and analyzed. Whole exome sequencing was performed in related family member. Western Blot was used to detect the effect of mutation on NRAP protein expression. The effect of c.259delC variant on myocardial development was further evaluated in zebrafish model . Results: A novel homozygous frameshift mutation c.259delC of NRAP was found in the proband with LVNC. It was found that c.259delC decreased the expression of NRAP by Western Blot. In the zebrafish model, the heart development was affected while knocking out NRAP gene, which showed pericardial edema. The pathological manifestations were uneven hypertrophy, disordered arrangement of cardiomyocytes, enlarged intercellular space and loose muscle fibers. The RNA-seq sequencing showed that the expression of genes related to heart development decreased significantly. And NRAP gene mutation could participate in the biological processes such as myocardial contraction, cell adhesion, myosin coarse filament assembly of striated muscle, myosin complex composition, muscle α-actin binding and so on. Conclusion: We identified a rare case of LVNC associated with a novel homozygous NRAP frameshift variant. The study further strengthened the evidence linking mutations in NRAP gene with LVNC, providing a new clue for further study of LVNC. NRAP may be one of the pathogenic genes of cardiomyopathy.